Impact on nonlinear/linear optical and structural parameters in quaternary In15Ag10S15Se60 thin films upon annealing at different temperatures. Issue 11 (1st June 2022) - Parida, Abinash; Sahoo, D.; Alagarasan, D.; Vardhrajperumal, S.; Ganesan, R.; Naik, R.
Abstract: In the present study, the effect of thermal annealing on structural, linear, and nonlinear optical properties of quaternary chalcogenide In15 Ag10 S15 Se60 thin film has been reported. The bulk sample synthesized by the melt quenching technique was used for the thin film preparation by the thermal evaporation method. Post deposition, the thin films were annealed at different temperatures like 100 °C, 150 °C, 200 °C, and 250 °C for 2 hs. X-ray diffraction (XRD) and Raman spectroscopy were used for structural studies, which showed the increase in crystalline phases with the increase of annealing temperature. The morphological images taken by field emission scanning electron microscope (FESEM) showed the densification and enlargement of scattered grains for annealed films. Furthermore, the constituent elements and their percentage in the sample were confirmed by Energy dispersive X-ray analysis (EDX). The linear and nonlinear optical parameters were calculated from the transmittance data obtained from UV–Vis spectroscopy in the wavelength range of 600–1100 nm. There is a large reduction in third-order nonlinear susceptibility at the higher annealing temperature. Subsequently, the transmission increased, whereas the absorption decreased with the annealing temperature. The extinction coefficient decreased while there was an increase in optical bandgap for the annealed films due to the decrease in surface defects and disorder, which forms the localized states in the bandgap. The oscillator energy, dispersion energy, dielectric constant, optical conductivity were calculated and discussed in detail. The change in both linear and nonlinear parameters by thermal annealing could be useful for controlling the optical properties of In15 Ag10 S15 Se60 thin film, which could be the preferable candidate for numerous photonic applications.